The DR-CAFTA and the Extensive Margin : A Firm-level Analysis - Molina, Ana Cristina; Bussolo, Maurizio; Iacovone, Leonardo (2012)
This paper examines the export behavior of Dominican Republic exporters following the implementation of the Dominican Republic-Central America Free Trade Agreement in 2007. Using a firm-level dataset for 2002-2009, the authors investigate the effects of a tariff reduction on the extensive margin. The analysis distinguishes the impact on the entry of new firms, exports of new products, and entry into the Agreement s markets. The paper analyzes whether the agreement prevents incumbent exporters from exiting the market. The results suggest that tariff cuts had a positive although very small effect on the extensive margin. A decline in tariffs also seems to reduce the probability of exit, but the effect is also small. The evidence calls for complementary policies aiming at helping exporters maximize the benefits of the agreement.